Pelatihan Peningkatan Keterampilan Literasi Keuangan Digital bagi Ibu-ibu Rumah Tangga - Eska Prima Monique Damarsiwi; Karona Cahya Susena; Nenden Restu Hidayah; Muhammad Rahman Febliansa; Yudi Irawan Abi (Universitas Dehasen Bengkulu, 2023)
Family is one of the smallest elements in society. The family itself consists of wife, husband and child, where each member of this family has their respective rights and obligations and roles. A father has a role to give a living to an ex-gan and set an example for his child and wife. Whereas as a mother also has an important role in the family. A wife has the role of organizing and managing what is needed in the household, educating children, and helping husbands maintain the household. Based on observations of the family financial recording team used by RT mothers . 31 RW. 07 The Wide Outpouring of the Great Ratu Kota Bengkulu District is still done manually so that there is often an irregular difference in financial calculations and records. Based on the results of observations made by the Dehasen University School of Economics Community Service Team, the swelling felt the need for efforts to be made in order to increase the knowledge of digital financial literacy of RT housewives . 31 RW. 07 Wide Rice Outpouring of the Great Ratu Bengkulu District. As for the efforts to be made, namely providing knowledge about counseling and training in how to practice in the operation of digital financial instruments. Devotional activities carried out by the team on RT mothers . 31 RW. 07 Wide Rice The Great Ratu Bengkulu sub-district is carried out through 2 stages. The first stage: problem identification, lectures and training, introduction and practice of digital financial applications, mentoring the preparation of family financial statements. Whereas the second phase of the team evaluates the learning outcomes of RT housewives . 31 RW. 07 Wide Rice Extent of the Great Ratu Bendangulu District with a post test result of 65% of participants able to answer questions raised by the team in the questionnaire. This shows the nautical as a great mother and mother able to understand the material provided during this PKM activity.